103 Effect of Floor Feeding Creep Feed on the Growth Performance and Morbidity and Mortality of Pigs After Weaning. (12th April 2022) - Wensley, Madie R; Tokach, Mike D; Goodband, Robert D; Gebhardt, Jordan T; Woodworth, Jason C; DeRouchey, Joel M; Allerson, Matt W; Menegat, Mariana
Abstract: A total of 264 litters corresponding to 2, 497 nursery pigs were used in a 40-d trial to determine the effect of floor feeding pelleted creep feed or lactation feed on the growth performance and morbidity and mortality of pigs after weaning. Treatments were applied in the farrowing house for 4-d prior to weaning and consisted of a control (no creep), standard (0.32 cm) creep pellet, large (1.27 cm) creep pellet, or sow lactation feed in meal form. For each treatment, approximately 227 g of creep feed per day equally divided into 2 feedings was provided on the mat in farrowing stalls. At weaning, pigs were transported to the nursery facility and randomized to pen within creep feeding treatment. A total of 96 pens (48 feeders) were used, with one barrow pen and one gilt pen per feeder. Thus, feeder (2 pens) was the experimental unit. There were 26 pigs per pen and 12 replications per treatment. During week 1 post-weaning, pigs fed standard or large pellet creep feed had increased ( P < 0.001) ADG compared with pigs fed sow lactation feed or no creep feed. This was not driven by improved ADFI but rather G:F ( P < 0.001). No differences in growth performance were observed throughout the remainder of the nursery period. Overall, on a per pig placed basis, pigs fed large pellet creep feed had increased ADG ( P < 0.05) and improved G:F ( P < 0.05) compared with pigs fed sow lactation feed, with the other 2 treatments intermediate. This response was a direct reflection of decreased ( P < 0.05) total mortality and removals for pigs fed large pellet creep feed. In summary, floor feeding large pellet creep feed starting 4-d preweaning improved nursery pig growth performance and fallout rates compared with creep feeding sow lactation feed, with standard pellet creep feed or no creep feed having an intermediate effect.